2001
DOI: 10.1111/j.1749-7345.2001.tb00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Compensatory Growth to Enhance Production in Channel Catfish Ictalurus punctatus

Abstract: Four treatment groups that received repeating cycles of fixed feed deprivation for either 0, 1, 2, or 3 d (control, treatment 1, treatment 2, and treatment 3, respectively), followed by periods of refeeding with a 36% protein commercial catfish feed once daily as long as the active phase of compensatory growth (CG) persisted, were assessed in flow‐through aquaria. No‐feed periods elicited the CG state and were immediately followed by days of ad libatum refeeding. At the end of 10 wk, average growth rate (AGR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 21 publications
2
47
0
4
Order By: Relevance
“…Compensatory growth continues to be of considerable interest as a method for increasing fish growth rates, improving feed conversion efficiency, decreasing waste production, and employing more convenient feeding schedules (Chatakondi and Yant 2001;Nikki et al 2004;Tian and Qin 2004). Optimal use of bioenergetics models in culture settings (Knights 1985) will probably require that models have the capacity to accurately forecast fish growth rates under feeding regimes designed to elicit and maximize CG.…”
Section: Resultsmentioning
confidence: 99%
“…Compensatory growth continues to be of considerable interest as a method for increasing fish growth rates, improving feed conversion efficiency, decreasing waste production, and employing more convenient feeding schedules (Chatakondi and Yant 2001;Nikki et al 2004;Tian and Qin 2004). Optimal use of bioenergetics models in culture settings (Knights 1985) will probably require that models have the capacity to accurately forecast fish growth rates under feeding regimes designed to elicit and maximize CG.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments on channel catfish, in which fixed periods of deprivation and re-feeding were used, have demonstrated either full or partial but not overcompensation (Kim and Lovell, 1995;Gatlin, 2000, 2001;. However, Chatakondi and Yant (2001) have reported growth over-compensation in channel catfish using a protocol similar to that used by Hayward et al (1997), in which a fixed number of days of deprivation was followed by a variable number of days of refeeding, with feeding continued for as long as the hyperphagia persisted. In the channel catfish, over-compensation was reported for deprivation periods of 1, 2 and 3 days.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that after a single period of 1 or 2 weeks of feed deprivation, the gibel carp can show full compensation when returned to a satiation ration (Qian et al, 2000;Xie et al, 2001). There is no comparable information on the longsnout catfish, although studies on the channel catfish, Ictalurus punctatus (Ictaluridae), have demonstrated compensatory growth in one catfish species (Kim and Lovell, 1995;Gatlin, 2000, 2001;Chatakondi and Yant, 2001). As part of a study on the effect of feeding schedules on the growth in live weight of gibel carp and longsnout catfish, the present experiment investigated the capacities of the two species to show compensatory growth in live weight as a response to cycles of deprivation and re-feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Hayward et al (1997) reported that hybrid sunfish (Lepomis cyanellus × L. macrochirus) subjected to repeating cycles (2 or 14 days) of no feeding and refeeding overcompensated only when the fish experienced the fixed no-feed periods of either 2, 4, 6, 10, or 14 days followed by periods of refeeding, as compared to fish fed meal worms Tenebrio molitor to satiation daily for 105 days. Additionally, channel catfish with 3-day feed deprivation only overcompensated, as compared to fish with daily satiation feeding when fish were fed a 36% protein commercial catfish feed to satiation daily or received repeating cycles of fixed feed deprivation for either 1, 2, or 3 days followed by periods of refeeding for 10 weeks (Chatakondi and Yant, 2001).…”
Section: Preparation Of the Experimental Dietsmentioning
confidence: 99%